Authority of Administrative Court in Establishing Administrative Sanctions for Local Government Officials Who Do Not Implement Administrative Court Verdict - Saputra, Bima; Hadiyantina, Shinta; Susmayanti, Riana (IJBLE Scientific Publications Community Inc., 2025)
This study is motivated by the lack of adherence among local government officials in executing decisions issued by the Administrative Court (PTUN). Furthermore, there is a legal inconsistency between Law Number 51 of 2009, which amends Law Number 5 of 1986 on Administrative Courts, and Law Number 30 of 2014 on Government Administration. This discrepancy concerns the sanction mechanisms for government officials who disregard PTUN rulings, potentially leading to ineffective enforcement. The research aims to examine the existing administrative sanction regulations and develop an optimal sanction framework for local government officials who fail to comply with PTUN decisions. Utilizing a normative approach, the findings reveal two distinct methods for enforcing administrative sanctions. Consequently, the author advocates for regulatory reform by redefining Administrative Court authority, enabling it to impose administrative sanctions on non-compliant officials. This adjustment is intended to reinforce the principle of separation of powers and ensure legal certainty.